2020
DOI: 10.1158/1078-0432.ccr-20-1434
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment Composition and Severe Cytokine Release Syndrome (CRS) Influence Toxicity in Patients with Large B-Cell Lymphoma Treated with Axicabtagene Ciloleucel

Abstract: Purpose: One of the challenges of adoptive T-cell therapy is the development of immune-mediated toxicities including cytokine release syndrome (CRS) and neurotoxicity (NT). We aimed to identify factors that place patients at high risk of severe toxicity or treatment-related death in a cohort of 75 patients with large B-cell lymphoma treated with a standard of care CD19 targeted CAR T-cell product (axicabtagene ciloleucel). Experimental Design: Serum cytokine and catecholamine levels were measured prior to lymp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 35 publications
(76 reference statements)
1
43
0
Order By: Relevance
“…A total of 26 studies reported the efficacy and/or safety of the three products in the treatment of DLBCL ( 16 , 17 , 19 , 22 , 23 , 26 31 , 34 36 , 38 47 , 49 , 50 ). The ORR of the three products for DLBCL was 70% (95% CI: 0.63–0.76; I 2 = 71.7%, P < 0.01), and response rate was 75% (95% CI: 0.67–0.83; I 2 = 66.0%, P < 0.01), 53% (95% CI: 0.44–0.61; I 2 = 0.0%, P = 0.88), and 72% (95% CI: 0.65–0.78) in axi-cel, tisa-cel, and liso-cel groups, respectively ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 26 studies reported the efficacy and/or safety of the three products in the treatment of DLBCL ( 16 , 17 , 19 , 22 , 23 , 26 31 , 34 36 , 38 47 , 49 , 50 ). The ORR of the three products for DLBCL was 70% (95% CI: 0.63–0.76; I 2 = 71.7%, P < 0.01), and response rate was 75% (95% CI: 0.67–0.83; I 2 = 66.0%, P < 0.01), 53% (95% CI: 0.44–0.61; I 2 = 0.0%, P = 0.88), and 72% (95% CI: 0.65–0.78) in axi-cel, tisa-cel, and liso-cel groups, respectively ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…Since many of the included studies simultaneously reported more than one tumor type as listed in Table 2, therefore, we divided them into different groups based on the type of tumor for analysis. For studies that did not report efficacy and safety results by type of tumor, we grouped them by their major tumor type (19,26,27,(43)(44)(45)(46)(47)50). Case series that involved fewer than four patients after regrouping were excluded from analysis (Table 3).…”
Section: Subgroup Analysis Based On the Type Of Tumormentioning
confidence: 99%
“…In addition to the key role of macrophage-produced cytokines in CRS, macrophage release of catecholamines can also mediate CAR T-cell therapy-related toxicities. An association was seen between patients with high peak levels of noradrenaline (NAD) following administration of standard of care axicabtagene ciloleucel (axi-cel) and grade ≥3 CRS, suggesting a link between catecholamine production and clinical toxicity ( 43 ). In a model by Staedtke et al., CRS was accompanied by a catecholamine surge and inhibition of catecholamine synthesis protected mice from fatal CRS ( 44 ).…”
Section: The Role Of the Tme In Car T-cell Therapymentioning
confidence: 99%
“…In these cohorts of patients, 43% -62% of patients would have been ineligible for the original ZUMA-1 trial due to patient or disease characteristics including renal insufficiency, decreased ejection fraction, thrombocytopenia, hyperbilirubinemia, symptomatic pleural effusion, chronic hepatitis B or C infection, HIV, prior CNS disease, prior allogeneic transplant, venous thromboembolism within 6 months, poor performance status, prior checkpoint inhibitor use, prior CD19 or CD20 directed therapy, variant histology, or use of bridging therapy 2,6-8 . 93% of patients in the Nastoupil study who completed leukapheresis ultimately received axi-cel comparable to the 91% of patients receiving the product in the original ZUMA-1 trial. In the real-world cohorts, the manufactured axi-cel product did not meet commercial release specifications in 3%-11% of cases, these patients were treated under the ZUMA-9 expanded access study 2,[6][7][8] .…”
Section: Challenges Post Us Fda Approval Of Car T Therapymentioning
confidence: 99%